2010
DOI: 10.1111/j.1462-5822.2010.01512.x
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium botulinum C2 toxin is internalized by clathrin- and Rho-dependent mechanisms

Abstract: SummaryClostridium botulinum C2 toxin is an ADPribosyltransferase, causing depolymerization of the actin cytoskeleton in eukaryotic cells. The C2 toxin is a binary toxin consisting of the enzymatic subunit C2I and the binding subunit C2II. Proteolytical activation of the binding subunit triggers the formation of heptameric structures (C2IIa), which bind to cellular receptors. C2I is able to bind to C2IIa oligomers, and it has been suggested that the whole complex is internalized by a raft-dependent mechanism. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 59 publications
1
36
0
Order By: Relevance
“…Interestingly, C2IN-Stv13 showed partial co-localization with a transferrin-Alexa 647 conjugate, a marker for clathrin-mediated endocytosis (Wittrup and Belting 2009). This finding is consistent with a recent study by Pust and co-workers showing that C2 toxin is internalized by clathrin-and Rho-dependent mechanisms (Pust et al 2010). As expected, C2IN-Stv13 uptake is only marginal in the absence of C2IIa which is in line with the results obtained by cell fractionation and may result from nonspecific pinocytosis.…”
Section: Uptake Of C2in-stv13 Into the Cytosol Of Cancer Cellssupporting
confidence: 94%
See 1 more Smart Citation
“…Interestingly, C2IN-Stv13 showed partial co-localization with a transferrin-Alexa 647 conjugate, a marker for clathrin-mediated endocytosis (Wittrup and Belting 2009). This finding is consistent with a recent study by Pust and co-workers showing that C2 toxin is internalized by clathrin-and Rho-dependent mechanisms (Pust et al 2010). As expected, C2IN-Stv13 uptake is only marginal in the absence of C2IIa which is in line with the results obtained by cell fractionation and may result from nonspecific pinocytosis.…”
Section: Uptake Of C2in-stv13 Into the Cytosol Of Cancer Cellssupporting
confidence: 94%
“…After assembly of C2IIa with the C2I moiety, the C2IIa/C2I complex binds to its cell surface receptor, an asparagine-linked carbohydrate structure found in all eukaryotic cell types tested (Eckhardt et al 2000;Kaiser et al 2006). This results in receptor-mediated endocytosis of the toxin, which has recently been shown to be clathrin and Rho dependent and to involve PI3K-Akt signaling (Simpson 1989;Nagahama et al 2009;Pust et al 2010). Owing to the acidification of the endosomal lumen, C2IIa undergoes a conformational change and is inserted into the endosomal membrane forming a pore.…”
Section: Introductionmentioning
confidence: 97%
“…C2I binds either to cell-bound C2IIa or to soluble C2IIa, and then the preformed C2IIa/ C2I complex can bind to the receptor what might enhance C2 toxin efficiency (Kaiser et al 2006). In any case, the receptor-bound C2IIa/C2I toxin complexes are internalized by receptor-mediated endocytosis (Pust et al 2010), and after transport by the vesicular protein traffic system, C2I translocates from acidified endosomal vesicles into the cytosol (see Fig. 1).…”
Section: Binary Exotoxins and Their Uptake Into Mammalian Cellsmentioning
confidence: 99%
“…However, there is increasing evidence that membrane translocation of other toxins, such as diphtheria or anthrax toxins, is facilitated by cytosolic host cell factors. First, Lemichez and co-workers showed in 1997 that a host cell protein (β-COP) is involved in the cellular uptake of diphtheria toxin (Lemichez et al 1997), and in 2003, Ratts and co-workers demonstrated that Hsp90 and thioredoxin reductase facilitate membrane translocation of this toxin from endosomal vesicles (Ratts et al 2003(Ratts et al , 2005. More recently, Tamayo et al reported that β-COP facilitates translocation of anthrax lethal factor across vesicular membranes in vitro (Tamayo et al 2008).…”
Section: Introductionmentioning
confidence: 96%
“…The binding component is proteolytically activated and forms heptamers, which interact with the enzymatic component (8, 10). After binding of the toxin to a cell surface receptor, the toxin complex is endocytosed (11,12). At low pH of endosomal compartments, the binding component inserts into the membrane of endosomes and forms pores, which allow the translocation of the enzymatic component into the cytosol (10, 13).…”
mentioning
confidence: 99%